Evaluating a commonly used tool for measuring sport specialization in young athletes - Miller, M.; Malekian, B. S.; Burgess, J.; LaBella, C. (Journal of Athletic Training, 2019)
Context Sport specialization has been defined as year-round intensive training in a single sport to the exclusion of other sports. A commonly used survey tool created by Jayanthi et al, which classifies athletes as having a low, moderate, or high level of specialization, categorizes only athletes answering yes to "Have you quit other sports to focus on a main sport?" as highly specialized. We hypothesized that a measureable number of year-round, single-sport athletes have never played other sports and, therefore, may be inaccurately classified as moderately specialized when using this tool, even though most experts would agree they should be viewed as highly specialized.